The state of the choroid in children with anterior uveitis assessed by optical coherence tomography - L. A. Katargina; E. V. Denisova; O. V. Novikova (Российский офтальмологический журнал)
Purpose: to analyze quantitative indicators and qualitative changes of the choroid in children with anterior uveitis as measured by optical coherence tomography (OCT) and assess the possibility of using the identification of opportunities for their use in evaluation of uveitis activity and the course of disease. Material and methods. 24 children diagnosed with anterior uveitis (38 eyes), aged 6 to 17, underwent standard ophthalmological examination and OCT scanning with an enhanced depth image module (OCT-EDI). The thickness of the choroid was measured manually by one researcher in 5 points: in the subfoveolar zone and at a distance of 3 mm from the fovea nasally, temporally, upwards and downwards. Most of the patients (20 children, 31 eyes) underwent a follow-up OCT to evaluate the choroid at diverse times since the start of the inflammatory process and for diverse degrees of its activity. OCT values were also compared with literature data on normal eyes. Results. For all areas studied, the thickness of the choroid was significantly higher in eyes with active and moderate inflammation than in those with remission of uveitis, and higher than in healthy eyes. The average subfoveal thickness of the choroid in eyes with active, moderate, subactive uveitis and with remission of uveitis was 398.80 ± 85.94, 413.61 ± 73.89, 368.53 ± 68.54 и 338.53 ± 51.50 μm, respectively (in healthy eyes — 341.96 ± 74.70 μm). A moderately strong positive correlation was found between the choroidal thickness and uveitis duration for subfoveal, nasal and suprafoveal points of measuring. Conclusion. A correlation between the choroid thickness and uveitis activity and duration was detected, indicating the involvement of the choroid in the inflammation process. Due to noticeable variability of the data caused by a variety of factors, a dynamic measuring of choroid thickness is recommended for evaluating uveitis activity and course of the disease as well as treatment planning. The OCT method of choroid thickness measurement should be included in the regular examination of children with anterior uveitis.